UJI INTERAKSI KIMIAWI PADA PROSES SORPSI ESCHERICHIA COLI DALAM KONDISI JENUH - Yunus Fransiscus (Department of Environmental Engineering-Faculty of Civil, Environmental and Geo Engineering. Institut Teknologi Sepuluh Nopember, Surabaya, 2006)
A study to describe the sorption characteristic of Escherichia coli was carried out in dynamic column experiments. Iron coated sand was used as the collector and phosphate was used to evaluate the attachment mechanism. The hypothesis that ligand exchange played significant role in the attachment mechanism was supported by observation of several phenomena: pH increase during the process, less detachment during the desorption, no significant effect of ionic strength and pH of the solution, and less attachment of E. coli in competition with phosphate. However, from the breakthrough curves it was indicated that ligand exchange was not the only process involved. The results gave an indication that bacterial retention in solid-liquid interface can be explained beyond the DLVO theory.